Chryseobacterium indologenes bacteremia in a healthy 2-month-old baby. Issue 2 (April 2021) - Caballero Mora, Francisco J.; Malgorzata Dyląg, Margarita; Ariza Jimenez, Ana B.; Jimenez Alvarez, Silvia M.
Abstract : N/A: Chryseobacterium indologenes is a Gram-negative bacteria rarely pathogenic in humans that can produce serious infections, especially, in children with comorbidities. Only a few cases of bacteremia have been published by C. indologenes, the majority in Taiwan. We show a Spanish healthy 2-month-old baby, who was diagnosed with this germ at our hospital, to report on the serious infections that it can cause and the multiple drug resistance to antibiotics that it shows.